Proton Versus Photon Radiation Therapy for Nasopharyngeal Carcinoma - Abiri, Arash; Liu, Derek; Pang, Jonathan Chung-en; Nguyen, Theodore V.; Bitner, Benjamin F; Torabi, Sina; Kuan, Edward C (Journal of Neurological Surgery Part B: Skull Base)
Objectives: Local treatment for nasopharyngeal carcinoma (NPC) commonly entails a regimen of radiotherapy. Due to its proximity to critical neurovascular structures, radiotoxicity presents a challenge. Proton radiotherapy (PRT) is associated with reduced toxicity and shows promise as an alternative to photon radiotherapy (XRT). Herein, we evaluated the therapeutic efficacies of PRT and XRT in NPC patients. Study Design: Retrospective database study. Methods: The 2004-2017 National Cancer Database was queried for patients with NPC who were treated with PRT or XRT. Using propensity score matching (PSM), patients who received XRT were matched in demographics and clinical characteristics with those who received PRT. Overall survival (OS) was assessed with Cox proportional-hazards regression and Kaplan-Meier analysis. Results: Of 7003 patients (6953 XRT, 50 PRT), 1946 (27.8%) were female with a mean age of 55.7±14.0 years. PSM resulted in 96 patients, with a large representation of T4 (57.3%), M0 (91.7%), and WHO type I (54.2%) tumors. Patients who underwent PRT were, on average, farther away from their treatment facility than XRT patients (101.7 vs. 14.0 miles; p<0.001). The 2-year OS rates for the PRT and XRT cohorts were 83.9% and 53.9%, respectively (p=0.002). Additionally, PRT was associated with significantly reduced mortality compared to XRT (HR 0.338; p=0.002). Conclusions: NPC patients demonstrated higher OS following PRT compared to XRT. Prospective trials consisting of larger and more heterogeneous patient populations are warranted to better delineate the therapeutic efficacy of PRT and direct its appropriate use as a primary radiation modality for NPC patients.